Jual Beli Tanah Yang Masih Dalam PPJB Perspektif Ekonomi Syariah - Ridlo, Ali (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
This research aims to describe the practice of buying and selling land carried out by sellers to other parties, even though the land was previously the object of sale and purchase with previous parties in the PPJB. The research methodology employed is qualitative research with a case study approach. The findings of this research indicate that land sale and purchase transactions (mutsman) conducted by the seller (al-ba'i) with buyers (al-Musytari) still within the PPJB with other parties constitute a form of buying and selling that does not align with the pillars and conditions of transactions in Sharia economics. The object of sale and purchase (mutsman) that is resold by the seller (al-ba'i) must be owned outright, or if not owned, permission must be obtained from the rightful owner. The resale of goods (mutsman) previously purchased by another individual is prohibited for the seller (al-ba'i) to the buyer (al-Musytari). Consequently, the sale and purchase are deemed invalid.